Scoping Review: Pregnant Women with HIV: Difficulties Faced and Coping Strategies - Idaningsih, Ayu; Handayani, Hilda; Urbaningrum, Bambang Amelia Fajriati; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi (Newinera Publisher, 2025)
Since the beginning of the case, the human immunodeficiency virus (HIV) has grown dramatically on a global scale. Pregnant women with HIV are one of the groups that receive worse negative impacts due to changes in health and social life due to being infected with HIV. Several studies have revealed coping strategies that pregnant women with HIV carry out to continue their lives. Therefore, this scoping review aims to identify coping strategies carried out by pregnant women in facing difficulties after being diagnosed with HIV. The study was established based on a scoping review framework by Arskey and O'Malley. Article searches were carried out on the MEDLINE and Scopus databases in early 2023. The selection of articles refers to inclusion criteria which include: the results of research on coping strategies carried out by pregnant women with HIV in facing difficulties, having a full text in English, and published in 2014-2023. The results of the analysis of 18 selected studies found two themes related to pregnant women diagnosed with HIV, namely the difficulties faced by pregnant women with HIV and coping strategies carried out by pregnant women with HIV. Almost all pregnant women with HIV have faced difficulties in controlling their negative emotions and stigma about HIV. However, positive coping strategies make pregnant women with HIV improve and live their next lives. The experience of pregnant women with HIV who have successfully faced their difficulties with positive coping strategies needs to be considered by the government and health service providers in managing the reduction of HIV prevalence.